Application of Moodle E-learning Platform in teaching of the course of Health Assessment for nursing students upgraded from junior college to university (基于Moodle平台的教学模式在护理专升本《健康评估》教学中的应用) - LU Jianping (鲁剑萍); ZHANG Cuidi (张翠娣); SUN Huijun (孙慧君) (Journal of International Translational Medicine Limited, 2022)
Objective To introduce and explore the application of Moodle E-learning Platform in teaching of the course of Health Assessment for nursing students upgraded from junior college to university. Methods A cluster random sampling method was used to select students who were upgraded from junior college to university from grade 2021. Students from two classes were divided into two groups: study group(n=118) and control group (n=123). In the control group, the theoretical and practical curriculums were toughed in a traditional way, and the teaching mode based on Moodle E-learning Platform was introduced into in teaching of the course of Health Assessment in the study group. The outcomes of theoretical and practical tests were measured and compared between study group and control group. A questionnaire survey was conducted to assess students' satisfaction with teaching. Results Students in the study group achieved higher scores of physical examination practice and theoretical test compared with those in the control group (P＜0. 01). In the control group, 123 questionnaires were distributed and 120 effective questionnaires were recovered, with an effective recovery rate of 97. 56%. In the observation group, 118 questionnaires were distributed and 116 effective questionnaires were recovered, with an effective recovery rate of 98. 31%. The outcomes of questionnaire survey showed that scores of all dimensions of satisfaction assessment in the study group were higher than those in the control group (P＜0. 01). Conclusion An effective and interactive network course based on Moodle E-learning Platform can stimulate students' interest in learning and cultivate students' ability of problem-solving and cooperation skills. The Moodle E-learning Platform plays an important role in promoting the teaching reform and the cultivation of senior nursing talents. (目的 介绍和探讨基于Moodle平台的教学模式在专升本学生《健康评估》教学中的应用。方法 采用随机整群抽样, 选取学校2021级专升本护理专业两个班级的学生为研究对象, 分为试验组(n=118)和对照组(n=123)。对照组进行一学期的传统理论授课(32学时)和操作课学习(16学时); 试验组传统理论授课同对照组, 操作课程采用基于Moodle平台的教学模式。对比两组学生操作和理论成绩, 评价学生满意度。结果 试验组学生体格检查操作和理论成绩均高于对照组学生, 差异有统计学意义(P＜0. 01)。对照组发放问卷123份, 回收有效问卷120份, 有效回收率97. 56%, 向试验组发放问卷118份, 回收有效问卷116份, 有效回收率98. 31%。学生对课程教学满意度评价结果显示, 试验组学生所有维度评分均优于对照组, 差异有统计学意义(P＜0. 01)。结论 基于Moodle平台的教学模式能够建立一个有效的、交互性强的网络课程, 激发学生的学习兴趣, 培养学生探究问题和协作的能力, 对教学改革和培养高级护理人才有重要的促进作用。)